Putative Role of Red Wine Polyphenols against Brain Pathology in Alzheimer’s and Parkinson’s Disease - Caruana, Mario; Cauchi, Ruben; Vassallo, Neville (Frontiers in Nutrition, 2016)
Alzheimer’s disease (AD) and Parkinson’s disease (PD) are the most common age-related neurodegenerative disorders and hence pose remarkable socio-economical burdens to both families and state. Although AD and PD have different clinical and neuropathological features, they share common molecular mechanisms which appear to be triggered by multi-factorial events such as protein aggregation, mitochondrial dysfunction, oxidative stress (OS) and neuroinflammation, ultimately leading to neuronal cell death. Currently, there are no established and validated disease-modifying strategies for either AD or PD. Among the various lifestyle factors that may prevent or slow age-related neurodegenerative diseases, epidemiological studies on moderate consumption of red wine, especially as part of a holistic Mediterranean diet, have attracted increasing interest. Red wine is particularly rich in specific polyphenolic compounds which appear to affect the biological processes of AD and PD, such as quercetin, myricetin, catechins, tannins, anthocyanidins, resveratrol and ferulic acid. Indeed, there is now a consistent body of in vitro and in vivo data on the neuroprotective effects of red wine polyphenols showing that they do not merely possess anti-oxidant properties, but may additionally act upon, in a multi-target manner, the underlying key mechanisms featuring in both AD and PD. Further, it is important that bioavailability issues are addressed in order for neuroprotection to be relevant in a clinical study scenario. This review summarises the current knowledge about the major classes of red wine polyphenols and places into perspective their potential to be considered as nutraceuticals to target neuropathology in AD and PD.